2007
DOI: 10.1016/j.otohns.2006.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Combined modality therapy of esthesioneuroblastoma

Abstract: Multidisciplinary therapy of ENB should be considered, especially for Kadish C and high-grade lesions. Craniofacial resection (CFR), Intensity modulated radiation therapy (IMRT), and chemotherapy should be investigated in a multi-institution trial of ENB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 20 publications
3
43
0
12
Order By: Relevance
“…Given the rarity of ONB, most published series were retrospective and had a small number of patients (12)(13)(14)(15) and chemotherapy (17). In the present study, all patients had T4 ONBs; the OS and LC at 3 and 5 years were 88.4% and 70.3%, and 83.0% and 83.0%, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…Given the rarity of ONB, most published series were retrospective and had a small number of patients (12)(13)(14)(15) and chemotherapy (17). In the present study, all patients had T4 ONBs; the OS and LC at 3 and 5 years were 88.4% and 70.3%, and 83.0% and 83.0%, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…Mclean et al found that there is no any survival benefit when cisplatin plus etoposide was added to the surgery in patients with olfactory neuroblastoma (20). Conversely, there are retrospective studies that suggested the potential benefit of adjuvant chemotherapy in high grade and advanced stage disease (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados en términos de supervivencia y periodo libre de enfermedad a los 5 años, si estimamos su valor según la curva de Kaplan Meier, son de 74,1% y del 55,6% respectivamente. En los artículos de la literatura el rango de supervivencia a los 5 años se sitúa entre el 50-90% y el periodo libre de enfermedad entre el 45-90% 2,16,17,37,41,42,48,60 . Cabe decir que nuestra población de pacientes se encuentran la mayoría en estadíos avanzados de la enfermedad, 2 estadíos B y 9 en estadíos C de Kadish, por lo que nuestros resultados los consideramos satisfactorios.…”
Section: Discussionunclassified
“…Si tomamos como referencia las series más largas de ENB, el rango varía de un 10 al 32% 2,16,17,37,41,42,48,60 , siendo algunas de ellas de gravedad, no siendo así en nuestra serie (dos osteomielitis crónica del colgajo que se curaron tras la retirada del colgajo y una fístula de LCR que se resolvió tras el sellado del defecto dural con fascia lata).…”
Section: Discussionunclassified
See 1 more Smart Citation